Case report: Assessing criminal responsibility and recidivism risk in the behavioral variant of frontotemporal dementia - Karcher, Anouk; Hamza, Rayane; Jantzi, Camille (Frontiers in Psychiatry, 2024)
Frontotemporal dementia (FTD) affects the frontal and temporal lobes of the brain, leading to personality changes, language impairments, and behavioral disturbances, including impulsivity and disinhibition. Assessing responsibility and recidivism risk in forensic evaluations is challenging due to the evolving nature of FTD. Despite limited literature, we present a case of a 45-year-old man with no prior legal or medical history, who committed criminal acts due to behavioral changes linked to the behavioral variant of frontotemporal dementia (bvFTD). Initial assessment found him irresponsible, with a non-evaluable risk of recidivism. Subsequent evaluation showed a low recidivism risk based on clinical evolution. We discuss these findings considering existing literature and Swiss jurisprudence.